Teaching computational systems biology with an eye on quantitative systems pharmacology at the undergraduate level: Why do it, who would take it, and what should we teach? - Androulakis, Ioannis P. (Frontiers in Systems Biology, 2022)
Computational systems biology (CSB) is a field that emerged, primarily, as the product of research activities. As such, it grew in several directions, in a distributed and uncoordinated way. This is precisely what made the field appealing, and fascinating. The idea of not having to follow a specific path, but rather create one is what fueled innovation in the field. As the field matured, several interdisciplinary graduate programs emerged attempting to educate future generations of computational systems biologists. These educational initiatives were still trying to coordinate the dissemination of information across student populations that had already made the decision to specialize in this field. However, we are now entering an era where CSB, has established itself, as a valuable research discipline, it attempting to the next major step: enter undergraduate curricula. As interesting as this endeavor may sound, it comes with several difficulties mainly due to the fact that the field is not uniformly defined. In this manuscript, we argue that this diversity is in fact a major advantage and that several incarnations of an undergraduate level CSB biology could, and should, be developed tailored to programmatic needs. We will share our experiences with developing such a course as part of the curriculum in a Biomedical Engineering department.